Research status of limestone powder concrete - Sun, Jian; Liyan, Suo; Сан, Джиан; Ліян, Суо; Сан, Джиан; Лиян, Суо (Харківський національний автомобільно-дорожній університет, 2019)
According to expert research and engineering application at home and abroad, this paper summarizes the basic properties of limestone powder, lime powder in cement base material, accelerate the hydration effect, active effect and particle morphology effect mechanism, and lime-stone powder on the working performance of concrete, durability and the influence of mechanical properties.
Дослідження стану вапнякового порошку в бетоні
Исследование состояния известнякового порошка в бетоне
Keywords: limestone powder; material; concrete; durability; вапняковий порошок; матеріал; бетон; довговічність; известняковый порошок; материал; бетон; долговечность; 625.825; 10.30977/BUL.2219-5548.2019.86.2.14